O papel da cooperação internacional para o acesso à água na América Latina (2000-2020) - Rodrigues, Kerolaine Priscila da Silva (2022)
The present dissertation discusses the problem of guaranteeing access to water in Latin America and how International Cooperation can collaborate for this and aims to investigate and analyze the role played by International Cooperation in encouraging access to water in the affected region of Latin America. Exploratory research is carried out, through a bibliographic and documentary analysis based on global and regional conferences on the subject and international cooperation initiatives in the region. With this in mind, the work addresses the relationship between the physical and political problem of lack of access to water in the region and the phenomenon of water scarcity, since this creates the ideal scenario for the water problem to persist. From this list, water policies in the region and the contribution that International Cooperation, either the technical or the financial type, has on them are discussed. Finally, examples are given of the application of International Cooperation in projects to encourage access to water in the region, highlighting the cases of the Cooperation Fund for Water and Sanitation (FCAS) and the Dry Corridor in Central America. It is concluded, then, that International Cooperation can generate positive impacts and boost access to water in the region depending on its form of formulation and implementation and depending on the involvement of different actors throughout its process, as in the case of FCAS-funded initiatives.